Аналіз проходження тесту тюрінга - Прочухан, Д. В. (ХНУРЕ, 2023)
The article deals with the problem of the possibility of creating a machine with human thinking on the example of the Turing test. The attempts of scientists to successfully pass the experiment in the period from the date of its creation to the present time are analyzed. Both relatively successful attempts and failures are considered. Various aspects of the experiments are critically analyzed. Conclusions are made regarding the successful passing of the Turing test in accordance with the initial formulation of the problem.